UI Design of the Bantargadung Village Administrative Service Information System Using the Design Thinking Method - Vivi Safira; Arny Lattu; Carti Irawan (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – Administrative services in villages are essential to support public service activities for the community. However, administrative services in Bantargadung Village are still conducted manually, resulting in several problems such as slow service processes, difficulties in managing administrative data, and limited access to information for the community. Previous studies mostly focused on system development and service functionality, while limited studies specifically discussed UI design that involves both service providers and service users throughout the design process and translates user needs into interface design decisions. Therefore, this study aims to design a User Interface (UI) for a village administrative service information system using the Design Thinking approach based on user needs. Methods – This study applied the Design Thinking approach through five stages: empathize, define, ideate, prototype, and testing. Data were collected through observation and semi-structured interviews involving village officials and community members to identify user needs and service problems. The UI prototype was developed using Figma and evaluated using the System Usability Scale (SUS) involving 10 respondents consisting of village officials and community members. Findings – The usability evaluation obtained an average SUS score of 84, which falls within the Acceptable range, receives a Grade A rating, and is categorized as Excellent based on the SUS interpretation framework. The developed UI design demonstrated a good level of usability based on the initial evaluation conducted with village officials and community members. These findings provide preliminary evidence that the proposed UI design has the potential to support digital-based administrative services in village environments. Research implications – This study is limited to the UI prototype development stage and has not yet reached full system implementation. In addition, the usability evaluation involved a limited number of respondents within one village environment, which may affect the generalization of the findings. Therefore, broader testing and further system implementation are needed in future studies. Originality – This study emphasizes the design of a village administrative service UI by involving both village officials and community members from the user needs identification stage through usability evaluation. The study also demonstrates how user needs are translated into system features, user flows, wireframes, and interface designs using the Design Thinking approach.